SISTEMATIC RIVIEW GAMBARAN PENGETAHUAN LANSIA TENTANG OSTEOPOROSIS TAHUN 2020 - Nasipta Ginting; Lia Adelina Aritonang (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Elderly is an age that has a greater likelihood of experiencing autoimmune, this is based on the statement that the older you get or the older you are, the more likely you are to experience autoimmune. Osteoporosis is a disease with reduced bone mass density caused by several factors, one of which is an unhealthy lifestyle. Lack of knowledge of the elderly about osteoporosis tends to increase the incidence of osteoporosis. The purpose of this study was to describe the knowledge of the elderly about osteoporosis in 2020 with a systematic review technique. The research design used in this study is a systematic review. In the search results, found around 1,270 articles related to the description of the elderly's knowledge about osteoporosis. Based on these inclusion criteria, the researcher discussed 10 articles related to the description of the elderly's knowledge about osteoporosis. have good knowledge, the rest of the respondents have sufficient knowledge 75%, and respondents who have less knowledge 20.8%. Based on the level of knowledge of the elderly, the results studied above can be seen that most of the respondents have sufficient knowledge about osteoporosis. It can be interpreted that the elderly understand enough about osteoporosis, it's just that there are still a few shortcomings. It is hoped that health cadres can provide further information about osteoporosis so that they can increase the knowledge of the elderly to be good and improve the health status of the elderly.